LINGGA YONI JEJAK PERADABAN MASYARAKAT (JAWA, BALI) DARI PERSPEKTIF POSITIVISTIK - Sunoto Sunoto (Fakultas Sastra Universitas Negeri Malang, 2017)
Abstract: Lingga-Yoni artifact is found to be a part of various traces of Javanese civilization. The artifact was created and is still meaningful for Javanese society. Its meaning depends on the point of view taken. As a part of critical thought, there are several points of view selected to find the meaning of the lingga-yoni artifact, they are anthropological, formal-structural, mythological, philosophical, and positivistic. From the positivistic point of view, lingga-yoni artifact might be assessed as the basis of probability and causal laws viewed from the relevant construct of positivistic thoughts. Permalink/DOI: dx.doi.org/10.17977/um015v45i22017p155